Grokking deep Q-networks (Manning Publications, 2020)
Miguel Morales, the master of RL domain and the author of "Grokking Deep Reinforcement Learning", demonstrates how to make reinforcement learning more like supervised learning with the help of the popular algorithm Deep Q-Network, which is still one of the best performing DRL agents.